Association of high-sensitivity C-reactive protein and anemia with acute kidney injury in neonates - Zhang, Peiyao; Tong, Yuanyuan; Yuan, Deshan; Li, Yixuan; Jin, Yu; Bai, Liting; Gao, Peng; Wang, Wenting; Hu, Jinxiao; Duan, Xin; Liu, Jinping (Frontiers in Pediatrics, 2022)
Background: It remains unclear about the association of high-sensitivity C-reactive protein (hsCRP) and anemia with postoperative acute kidney injury (AKI) in neonates with congenital heart disease (CHD). The purpose of this study was to examine whether anemia-associated AKI is modulated by hsCRP in neonates. Methods: This study included 253 consecutive neonatal patients undergoing CHD surgery in a national tertiary hospital. We investigated the association between postoperative AKI with baseline hsCRP, anemia as well as their interaction by multivariable logistic regression analyses. Results: Incidence of AKI was 24.1% in the entire cohort. After being adjusted for covariates, hsCRP level was negatively correlated with AKI (P<0.01 for 1 mg/L threshold), whereas anemia emerged as an independent risk factor of AKI (P=0.02). Besides, there was a significant interaction between anemia and hsCRP level (P=0.01). In neonates with hsCRP<1 mg/L, anemia was positively associated with AKI (P=0.03). However, no significant association was found between anemia and AKI in the context of hsCRP≥1 mg/L. Combination of anemia and hsCRP<1 mg/L was independently correlated with risk of AKI (P<0.01), while concomitant anemia and hsCRP≥1 mg/L or hsCRP<1 mg/L combined with non-anemia was not. Conclusions: In neonates with CHD, risk of anemia-associated AKI may be modulated by hsCRP level. Attention should be paid to neonates with preoperative anemia and baseline hsCRP<1 mg/L to reduce the risk of postoperative AKI.